The Prevalence and Risk Factors of Type 2 Diabetes Mellitus among Adults in Itahari Sub-Metropolitan City of Eastern Nepal (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Diabetes Mellitus presents a substantial health challenge worldwide. Its prevalence has been increasing more rapidly in low and middle-income countries such as Nepal. Globally, the number of individuals affected by diabetes rose from 108 million in 1980 to 422 million in 2014. The study was aimed to assess the prevalence of Type 2 Diabetes Mellitus (DM) and explore the associated risk factors with Type 2 DM.Materials and Methods: A community-based cross-sectional study was designed to investigate the adult population of Itahari sub-metropolitan city in Sunsari district, Nepal. The study included individuals aged ≥ 18 years of both genders residing in Itahari sub-metropolitan city, an urban area of Sunsari District. Data collection was conducted through face-to-face interviews using a semi-structured, pre-tested WHO STEPS survey questionnaire. Collected data were entered into Microsoft Excel and then imported into the Statistical Package for Social Sciences (SPSS) for statistical analysis. Bivariate analysis was performed using the chi-square test and Fisher’s exact test.Results: Out of 322 participants, 64 (19.9%) individuals were diagnosed with Type 2 Diabetes Mellitus, either with or without hypertension. Among the diabetic participants, 39 (60%) had comorbid hypertension, while the remaining 25 (39.06%) did not exhibit hypertension.Conclusion: Anxiety and depression are common among elderly people living in community in urban Kathmandu. More than one third have both disorders.